Towards an enhanced nanocarbon crystallization from lignin. (25th January 2023) - Rocha, Douglas; Luzardo, Jéssica; Aguiar, Daniele; Massafra, Sanair; Valaski, Rogério; Silva, Alexander; Ferreira, Erlon; Simão, Renata; Archanjo, Bráulio; Kuznetsov, Alexei; Araujo, Joyce
Abstract: In this work, a new approach to the synthesis of lignin-derived nanocarbon crystals based on lignin depolymerization is proposed. The lignin chemical structure was modified through a controlled routine, which was based on sequential UV light irradiation, hydrothermal carbonization in autoclave, vacuum degassing, pyrolysis and mechanical exfoliation. In this way, we were able to obtain a lignin-based nanocarbon with a sp 2 -hybridized nanoporous framework structure with oxygenated functional groups attached to this structure. The used catalyst-free route resulted in high nanocarbon yields and turns out to be an eco-friendly strategy of a synthesis of low-cost carbon materials. The characterization of the lignin-derived nanocarbon was carried out using X-ray diffraction measurements, infrared, Raman and X-ray photoelectrons spectroscopies analyses. The nanocarbon materials' morphology was evaluated by scanning and transmission electron microscopy. The method of lignin's transformation developed in this work showed itself as a promising alternative for provision of large amounts of carbon-based materials for industrial applications. The proposed approach may be adapted to various biomass feedstocks with aromatic groups' content suitable for their high yield polycondensation. The achieved nanocarbon yield, when starting from a commercial purified lignin, varied between 50 wt% and 70 wt%. Graphical abstract: Image 1 Highlights: Lignin raw-material as a carbon source to produce lignin nanocrystals. Catalyst-free synthesis turns out to be an eco-friendly strategy. Synthesis provides high output: 50 wt% and 70 wt% yield. Methodology resulted in an integral conversion of lignin in a nanocarbon. Carbon sheets forming pores with the size within micropore and low mesopore ranges. .